Highly responsive photochromic behavior with large coloration contrast in Ba/Sm co-doped (K0.5Na0.5)NbO3 transparent ceramics. Issue 13 (1st July 2022) - Yu, Fangyuan; Chi, Yuan; Wang, Peng; Ma, Bowen; Wu, Xiao; Lin, Cong; Zhao, Chunlin; Gao, Min; Lin, Tengfei; Zhang, Qiwei
Abstract: Ferroelectrics that simultaneously possess optical transparency and photochromic (PC) behavior have attracted extensive attention for multi-functionality. However, inability to achieve both rapid and large coloration contrast in photo-stimulated ferroelectrics limits their practical application. In this work, we propose a new strategy for realizing rapid photochromism by constructing the intermediate trap level (T2 ) in Ba/Sm co-doped (K0.5 Na0.5 )NbO3 (KNN) ferroelectric transparent ceramics. Specifically, rapid photo-response time of about 2 s was achieved, and the modulation ratios of transmittance and luminescence intensity were 37.6% and 72.6% within 2 s for the ceramics. This highly responsive PC behavior with large coloration contrast is expected to broaden the application of PC materials in optical devices, e.g. photo-sensitive glasses and rewritable information displays.